The presence of theology in the civil university: challenges and possibilities - Villagrán, Gonzalo (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2016)
Drawing from the experience around the creation and development of Granada University’s Chair of Theology, an important achievement in the history of Spanish theology, this article reflects on the challenges related to the presence of theology in the civil university. We can classify these challenges in four groups: religious, cultural, socio-political and academic challenges. This article wants to offer at the same time some orientations, fruit of our experience at the Chair, in order to face each one of these challenges. Finally, this article presents a synthesis of the benefits for theology and for the civil university that spring from the presence of theology in the civil academic world. This presence allows the university to be more what it ultimately is.